Cardioprotective Activity of Agaricus bisporus Against Isoproterenol-Induced Myocardial Infarction in Laboratory Animals - Bhushan, Apoorva; Kulshreshtha, Mayank (Current Nutrition & Food Science, 2019)
Background: Agaricus bisporus (A. bisporus) is an edible basidiomycete mushroom native to grasslands in Europe and North America. A. bisporus, commonly known as white button mushroom (WBM), is widely cultivated in most countries, and it constitutes the bulk of all mushrooms consumed in the United States and Australia. Traditionally this fungus has used in the treatment of heart diseases. Also it has anti-ageing property.Mushrooms have been found effective against cancer, cholesterol reduction, stress, insomnia, asthma, allergies and diabetes. Objective: The present research was designed to appraise the cardioprotective activity of a hydroalcoholic extract of Agaricus bisporus (EEAB) on Isoproterenol (ISO) induced myocardial infarction (MI) in Albino Wistar rat. Traditionally, Agaricus bisporus is reported in the treatment of heart diseases, cancer, cerebral stroke and anti-ageing property. Materials and Methods: Wistar rats of different sex were randomly split into five groups namely positive control, negative control, standard, test-1 and test-2 and received distilled water, ISO (85 mg/kg), Simvastatin (10 mg/kg/day, oral) and EEAB (200 and 400 mg/kg/day, p.o.) for 30 days, respectively. MI was induced in rats by ISO at an interval of 24 hrs on 31 and 32 day and on the next day, blood was amassed through retro-orbital plexus for the assessment of biochemical markers (cholesterol, lowdensity lipoprotein, high-density lipoprotein, very low-density lipoprotein, triglycerides, alanine aminotransferase and total protein) and finally, the rats were immolated by cervical dislocation. The heart tissue was reaped instantly, cleaned with chilled isotonic saline and clasped in 10% buffered formalin and used for the histopathological analysis. Results: ISO p.o. administration significantly elevated the cholesterol, low density lipoprotein, very low density lipoprotein, triglycerides, alanine aminotransferase and aspartate aminotransferase levels while it decreases high-density lipoprotein and total protein in plasma and administration of EEAB decreases the level of cholesterol, low-density lipoprotein, very low-density lipoprotein, triglycerides, alanine aminotransferase and aspartate aminotransferase levels while it increases high-density lipoprotein and total protein levels. Pretreatment with EEAB protected the cardiotoxicity induced by ISO. The histopathological findings support the analysis of biochemical parameters, ISO-induced myocardium showed infracted zone with edema, inflammatory cells, lipid droplets, myocardial necrosis and vacuolization of myofibrils which were reduced. Conclusion: It can be an outcome that EEAB possessed cardioprotective activity against experimental and clinical studies of ISO-induced myocardial infarction in rats.
Keywords: myocardial infarction